Characteristics and failure analysis of a railway tunnel collapse influenced by cavity in phyllite strata. (December 2022) - Chen, Longlong; Wang, Zhi-Feng; Wang, Yaqiong; Bai, Xitong; Lai, Jinxing
Highlights: The failure characteristics of the tunnel collapse influenced by cavity in phyllite strata were analyzed. A 3D finite element model was established to simulate and analyze the failure mechanism of the tunnel collapse. The treatments of collapse were proposed and analyzed. Abstract: Tunnelling in phyllite strata with cavity is prone to collapse even with reasonable construction design. Based on a railway tunnel collapse influenced by cavity in phyllite strata, characteristics and failure mechanisms were analyzed by field investigation, in-situ monitoring and numerical simulation, and further explore the failure factors and treatments. The results show that tunnel excavation caused groundwater seepage towards the cavity, and the water invading induced phyllite dissolution and mechanical properties weakening of surrounding rock were mainly attributed to be the causes of the collapse. Based on the results, the treatments of surrounding rock grouting and steel arch replacing were adopted to ensure the stiffness and stability of tunnel structure. Finally, the treatment effectiveness is investigated combined with the monitoring data. The result facilitates prevention and treatment of collapse induced by underground tunnelling near ground fissures. The result contributes to prevention and treatment of tunnel collapse failure in phyllite strata.